Віртуальна власність крізь призму теорій права власності - Некіт, Катерина Георгіївна; Nekit, Kateryna G. (ВД "Гельветика", 2019)
У статті зроблено спробу проаналізувати можливість обґрунтування концепції права віртуальної власності за допомогою основних нормативних положень теорії права власності. Розглянуто трудову теорію, теорію утилітаризму й теорію свободи особистості як підстави існування права віртуальної власності. Зроблено висновок, що кожна з наведених теорій може бути застосована для обґрунтування можливості існування права власності на віртуальні активи. Наведено зарубіжну практику нормативного врегулювання відносин віртуальної власності.

The article attempts to analyze the possibility of justifying the concept of virtual property rights using the main regulatory theories of property rights. The labor theory, the theory of utilitarianism and the theory of individual freedom as the basis for the existence of the virtual property right are considered. The rationale for the possibility to apply property right provisions to virtual assets with the help of J. Locke’s theory is that players, spending a significant part of their time and effort while playing a game, actually invest their work in creating virtual objects. Skeptics objections that the game cannot be equated to work are refuted by the facts of high earnings of players in the real world (for example, football players, tennis players, etc.), for whom the game is the work itself. The fact that people in China earn money by playing virtual games also serves as an argument for the possibility of applying this theory to substantiate the right of virtual property. From the point of view of the theory of utilitarianism, the public good consists of individual benefits. Since millions of people invest their labor in creating valuable objects in virtual worlds, there is a basis for recognizing property rights based on the value of transactions for individual users. Thus, from the point of view of the social utility of avatars and virtual assets, utilitarianism gives grounds to consider these objects as property. The theory of individual freedom applies to virtual objects for two reasons. First, there are no particular differences between the accumulation of real and virtual values. Therefore, if the theory of personality gives grounds for recognizing the ownership of land or goods, it also gives grounds for recognizing the ownership of virtual land and goods. Secondly, if we consider that the right of ownership should arise where a person feels the continuation of himself into things, for virtual things the rationale proposed by the theory of personality is even more obvious than for real ones. It is well known how strongly people tend to associate themselves with their avatars and see in them the continuation of their personality. It is concluded that each of the theories presented can be used to justify the possibility of the existence of property rights to virtual assets. The foreign practice of normative regulation of virtual property relations is given.
Некіт К. Г. Віртуальна власність крізь призму теорій права власності / К. Г. Некіт // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 78-82
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; теорії права власності; віртуальна власність; трудова теорія; теорія утилітаризму; теорія свободи особистості; віртуальні активи; онлайн ігри; property theories; virtual property; labor theory; utilitarian theory; theory of individual freedom; virtual assets; online games